George Hasslein, Dean of Architecture, circa 1968-1983 (1968)
George Hasslein, Dean of the College of Architecture and Environmental Design, stands next to "Greek Maiden" frieze (sculpture) near the Architecture Building. The Greek Maiden was one of several statues relocated to Cal Poly after the restoration of the Palace of Fine Arts in San Francisco. Read more at the Mustang Daily, January 19, 1968 "Maybeck statues given to college" https://digitalcommons.calpoly.edu/studentnewspaper/1259/